(12-4x)+(5-7x)=23

Simple and best practice solution for (12-4x)+(5-7x)=23 equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for (12-4x)+(5-7x)=23 equation:


Simplifying
(12 + -4x) + (5 + -7x) = 23

Remove parenthesis around (12 + -4x)
12 + -4x + (5 + -7x) = 23

Remove parenthesis around (5 + -7x)
12 + -4x + 5 + -7x = 23

Reorder the terms:
12 + 5 + -4x + -7x = 23

Combine like terms: 12 + 5 = 17
17 + -4x + -7x = 23

Combine like terms: -4x + -7x = -11x
17 + -11x = 23

Solving
17 + -11x = 23

Solving for variable 'x'.

Move all terms containing x to the left, all other terms to the right.

Add '-17' to each side of the equation.
17 + -17 + -11x = 23 + -17

Combine like terms: 17 + -17 = 0
0 + -11x = 23 + -17
-11x = 23 + -17

Combine like terms: 23 + -17 = 6
-11x = 6

Divide each side by '-11'.
x = -0.5454545455

Simplifying
x = -0.5454545455

See similar equations:

| x^3+3*x+2=0 | | y=28-3(6) | | y=28-3(5) | | y=28-3(3) | | y=28-3(2) | | 20=40-4f | | 3(k+4)=12k-6 | | 6X+20=14x-68 | | x-6y=3v | | 76-7x=29x+16 | | 2x=8+2 | | 8(x+1)=2(x-2) | | 94-2x=25x+19 | | 8x-4=58 | | 7z-2=3z+6 | | 10-8x=82-29x | | 7x+5=54 | | 15-4e=3 | | 3e-3=18 | | 4x=88 | | 6x=88 | | -15-2x=13-9x | | 3y+3=18-2y | | 5-9x=45-23x | | 6x+39=16x-42 | | 5x+20=10x+10 | | 3(w-2)=12 | | 6a=17.4 | | 2a(3a-2)=0 | | 208-4x=32+20 | | t(4t-7)=0 | | 30+30*0+1=1 |

Equations solver categories